Predicting β-turns and their types using predicted backbone dihedral angles and secondary structures - Kountouris, Peter; Hirst, J.D. (BioMed Central Ltd, 2010)
Background: β-turns are secondary structure elements usually classified as coil. Their prediction is important, because of their role in protein folding and their frequent occurrence in protein chains.